Inhibition of hemolytic activity of the thermostable direct hemolysin of Vibrio parahaemolyticus by ganglioside. - Takeda, R (1975)
The hemolytic activity of the thermostable direct hemolysin produced by Vibrio parahaemolyticus was inhibited by a ganglioside mixture. The ganglioside component which inhibited the hemolysin was not FM1 ganglioside.